Development of sperm separation system using electrical current for bull - Farah Hanan Fathihah Jaffar; Siti Fatimah Ibrahim; Mohd Iswadi Ismail; Chew, Fang Nang; Syarifah Faezah Syed Mohamad; Nur Hilwani Ismail; Nurol Afiza Abdul Wahab; Balkhis Bashuri; Khairul Osman (Penerbit Universiti Kebangsaan Malaysia, 2019)
A novel electrophoretic separation system has been successfully applied for the preparation of human sperm prior to the execution of assisted reproductive techniques (ARTs). This new system is designed to overcome the generation of reactive oxygen species (ROS) through centrifugation in conventional sperm preparation. Since the previous study showed favorable outcomes in humans, this study intends to implement this new system for animal sperm preparation particularly in bull. Fresh semen from adult bulls were used. Optimization of the electrophoretic system for optimum bull sperm separation involved different strength of voltage and separation time. The voltages applied were 10V, 20V, 30V, 40V, 50V, and 60V. For each voltage applied, the system was operated for a duration of 12 min. An average of 10 μl fractionalized semen was taken out at the collection site at every 2-min interval. Every fractionated sperm was then evaluated for percentage of viability, motility, and DNA damage assessment. Result showed that electrophoresis at 20V and 6 min yielded more than 80% viable and more than 70% motile sperm population with the lowest DNA damage. In conclusion, the system was able to fractionate high quality bull sperm at 20V and 6 min.